What Edits Are Done on The Highly Answered Questions in Stack Overflow? An Empirical Study. - Jin, Xianhao; Servant-Cortés, Francisco Javier (IEEE, 2019)
Stack Overflow is the most-widely-used online question-and-answer platform for software developers to solve problems and communicate experience. Stack Overflow believes in the power of community editing, which means that one is able to edit questions without the changes going through peer review. Stack Overflow users may make edits to questions for a variety of reasons, among others, to improve the question and try to obtain more answers. However, to date the relationship between edit actions on questions and the number of answers that they collect is unknown. In this paper, we perform an empirical study on Stack Overflow to understand the relationship between edit actions and number of answers obtained in different dimensions from different attributes of the edited questions. We find that questions are more commonly edited by question owners, on bodies with relatively big changes before obtaining an accepted answer. However, edited questions that obtained more answers in a shorter time, were edited by other users rather than question owners, and their edits tended to be small, focused on titles and in adding addendums.
Keywords: Software - Mantenimiento; Empirical software engineering; Developer forums; Software maintenance